GAYA PENGASUHAN UNTUK MEMBANGUN KEMANDIRIAN ANAK AUTIS - Nazrina zahara; Suryani Hardjo; Afisah Warda Lubis; Meutia Nauly; Fillia Dina Anggaraeni (Jurnal Genta Mulia, 2026)
This study is a qualitative research on effective parenting styles of children with autism. In this studythere are some things you want investigated, namely: the form of parenting styles in children withautism who are independent and autistic children are not independent, and the kind of self-reliance inchildren. Data collection techniques used were interviews and observation. Respondents in this studyamounted to two people, the mothers of children with autism. The study involved the respondent'shusband, a child therapist respondent, the respondent children and teachers tk. The research wassupported by the theory of parenting styles, effective parenting styles theory to children with autismand theory of self reliance. Parenting style is the interaction between parents and children, namely howparental attitudes or behaviors when interacting with children including the application of rules againstchildren and teach values or norms. Effective parenting style parenting is the way that suits the needsof children including the application of rules against children; choosing appropriate strategies for thechild. Children with autism are children who have a tendency of behavior in which the child is lackingin social interaction, delayed language development, and has its own world. Independence is a skill tohelp themselves, both physically and psychologically self-reliance The results of this study concludedthat the Authoritarian and permissive parenting styles that have been applied to respondents for theirchildren I do not make the child independent, while the second respondent on parenting styles are authoritative parenting styles and effective parenting styles to make his son to become independent.